2008
DOI: 10.1007/s00424-008-0492-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and biophysical properties of Ca2+ channels and subtype distributions in human adrenal chromaffin cells

Abstract: In this study, we explored the pharmacological and biophysical properties of voltage-activated Ca2+ channels in human chromaffin cells using the perforated-patch configuration of the patch-clamp technique. According to their pharmacological sensitivity to Ca2+ channel blockers, cells could be sorted into two groups of similar size showing the predominance of either N- or P/Q-type Ca2+ channels. R-type Ca2+ channels, blocked by 77% with 20 muM Cd2+ and not affected by 50 muM Ni2+, were detected for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…In humans, chromaffin cells have an adrenergic phenotype (30) and they are the primary source for adrenaline production and release. In the human adrenal gland there is a juxtaposition of medulla and cortex (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, chromaffin cells have an adrenergic phenotype (30) and they are the primary source for adrenaline production and release. In the human adrenal gland there is a juxtaposition of medulla and cortex (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The present study was planned to explore the hypothesis that the mode of Ca 2ϩ entry through a given VDCC subtype, rather than the total amount of Ca 2ϩ entry into the cell, is more relevant to trigger endocytosis. We have used bovine adrenal chromaffin cells because they express the same densities of VDCC subtypes than human chromaffin cells (26,54), namely, 20% L channels, 30% N channels, and 50% PQ channels (28). Despite that L channels contribute to only 20% of total whole cell current through VDCCs (2,24), Ca 2ϩ entering through slowinactivating L-type channels seems to be functionally coupled to endocytosis.…”
mentioning
confidence: 96%
“…Consequently, chromaffin cells exhibit an adrenergic phenotype (Pérez-Alvarez et al 2008). In effect, when the different catecholamines preferentially released under different conditions were compared in sympathetic nerve and adrenal gland tissue, it was observed that insulin-evoked hypoglycemia and caffeine ingestion, in decreasing order of potency, predominantly induced the release of adrenaline from the adrenal medulla.…”
Section: Chromaffin Vesiclesmentioning
confidence: 98%
“…The voltage-dependent calcium channels expressed in human chromaffin cells are L-, N-, P/Q-type (Gandía et al 1998;Pérez-Alvarez et al 2008) and R-type channels (Pérez-Alvarez et al 2008). Two populations of cells can be sorted according to the major contribution of N-or P/Q-type channels (Pérez-Alvarez et al 2008), which allows for cell-type specific modulation.…”
Section: The Stimulus-secretion Coupling Processmentioning
confidence: 99%
See 1 more Smart Citation